'A Sexual Series'. Issue 3 (1st November 2021) - Elg, Emie // Eva-Marie
Sara Ahmed's enquiry on what it means for sexuality to be lived as oriented from the work Queer Phenomenology inspired the art series 'A Sexual Series', based on post-humanist theory and asexual experience. Shapes of performative alter egos materialized from a queer cyborg position of technologically enhanced crip experiences (the strong symbolical constructing process of straightening scoliosis surgery). From being a glitch of the past towards a post-individualist future, the artificial intelligence sexbot is a metaphoric, elevated cyborg drag version of the artist to embody asexuality and queer Otherness. Based on multitudes of CUNTraDICKtions to encourage self-reflection, the series explores the complexities of ob/scene and on/scene performances; the position of a sex positive asexual as well as questions of belonging as a naturally artificial rebel.